2008
DOI: 10.1271/bbb.70704
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hyperglycemic Activity of Kiwifruit Leaf (Actinidia deliciosa) in Mice

Abstract: The methanol extract of kiwifruit leaf suppressed the postprandial blood glucose level after an oral administration of soluble starch or sucrose in mice. The mechanism of action is proposed to be due to the alpha-amylase-inhibiting activity in the 90% aqueous methanol fraction and alpha-glucosidase-inhibiting activity in the n-buthanol fraction, based on the results of in vitro experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…Many food materials that contain inhibitors of carbohydrate-digestive enzymes are known, [10][11][12][13] but we have particularly been interested in inhibitors of glucose transport in the small intestine. Only few materials for functional foods have been reported as inhibitors of glucose absorption, such as gymnemic acids form leaf of Gymnema sylvestre, 14) and phloridzin from bark of apple tree.…”
Section: Discussionmentioning
confidence: 99%
“…Many food materials that contain inhibitors of carbohydrate-digestive enzymes are known, [10][11][12][13] but we have particularly been interested in inhibitors of glucose transport in the small intestine. Only few materials for functional foods have been reported as inhibitors of glucose absorption, such as gymnemic acids form leaf of Gymnema sylvestre, 14) and phloridzin from bark of apple tree.…”
Section: Discussionmentioning
confidence: 99%
“…The working mechanisms and active ingredients of these food materials need to be elucidated by fundamental research for their most effective application to maintain our health. Most materials have shown inhibitory activity against carbohydrate digestive enzymes as an active principle, i.e., in adzuki beans, 14) paschaca, 15) kiwifruit leaf, 16) and sugar maple leaf. 17) Part of our studies has shown PLE to significantly suppress the postprandial elevation of the blood glucose level in a dose-dependent manner after administering soluble starch (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Worldwide, many kinds of herbs are used for diabetic care [4,5] and in medicinal therapy for diabetes. To identify new compounds that may be useful for preventing or treating diabetes, we screened many kinds of natural products that exert an anti-hyperglycaemic effect and identified foods that may be useful for diabetic care, as described previously [6][7][8]. As part of these ongoing experiments, we found that an extract from the leaves of Acer pycnanthum had an anti-hyperglycaemic effect.…”
Section: Introductionmentioning
confidence: 99%